PENGARUH FASILITAS, HARGA DAN LOKASI TERHADAP KEPUASAN SISWA PADA SEKOLAH MENENGAH KEJURUAN MUHAMMADIYAH 1 KALIANDA - Tamam Tamam; Umar Sanusi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The condition of competition in the world of education, especially vocational high school education has begun to be felt by every vocational school. The problem faced by the Muhammadiyah Kalianda Vocational School at this time is the competition between Vocational Schools, especially State Vocational Schools which in accepting new students tend to accept new students with a large number of class capacities so that the choice to go to private schools is very small, including SMK Muhammadiyah 1 Kalianda, therefore for survival Private school life must be able to compete in a healthy manner with regard to facilities, prices and strategic locations in providing satisfaction to students. This study is to analyze the behavior of students in choosing Vocational High School (SMK) Muhammadiyah1 Kalianda, and aims to determine the effect of facilities, prices and location either partially or simultaneously on student satisfaction at SMK Muhammadiyah 1 Kalianda. The research was carried out using a quantitative survey method of student satisfaction at SMK Muhammadiyah 1 Kalianda. The population used in this study were students of SMK Muhammadiyah 1 Kalianda totaling 220 students. Sampling using the Slovin formula with a standard error of 10% = 69 samples. Sampling in this study was carried out using a proportionate stratified random sampling technique, which is a technique used when the population has members/elements that are not homogeneous and stratified proportionally. Instruments